PERAWATAN GIGI GELIGI PADA ANAK DENGAN GIGI LEBIH (LAPORAN KASUS) - Ike Siti Indiarti; Sri Harsini; Sarworini Bagio Budiardjo (Faculty of Dentistry, Universitas Indonesia, 2015)
The variation of teeth number can occur at initiation phase of tooth development, the etiology is unclear but it be supported by the excessive lamina dental activity. The supernumerary teeth can be single or multiple, at one side or two sies, with conical, tubercle or normal form, undergo eruption or impacted, and with parallel or contrary direction of teeth development. The supernumerary teeth in incisive region is mesiodens. In this case report, the supernumerary teeth occurred at mixed dentition period which it result in the tooth arrangement is bad. The mesiodens was extracted as the position of upper jaw central incisive teeth were corrected. The secon supernumerary tooth with contrary direction was removed by surgery.